Influence of Messa di Voce speed on vocal stability of untrained, healthy subjects - Kirsch, Jonas; Köberlein, Marie; Döllinger, Michael; Echternach, Matthias (PloS one, 2025)
Despite its importance in voice training, comprehensive research into sustained vowel phonation with constant pitch and increasing and decreasing loudness, the so-called Messa di Voce, is lacking. The study examines the laryngeal behavior during Messa di Voce, regarding the impact of the speed of execution on voice stability parameters. Nine untrained, healthy subjects (5 female, 4 male) were asked to perform Messa di Voce exercises on the vowel [i:], involving a gradual increase and decrease of volume. During the first task, each phase should take 3 s, whereas in the second task, each phase should take 1 s. Female subjects sang pitch B3 (fundamental frequency fo ≈ 247 Hz), and male subjects pitch B2 (fo ≈ 124 Hz). Throughout phonation, synchronous recordings were captured through high-speed videolaryngoscopy (HSV), electroglottography, and audio signals. Subsequently, the Glottal Area Waveform was extracted from the HSV data. The tasks' duration and calculated parameters (including, e.g., Open Quotient (OQ), Closing Quotient (ClQ), Relative Average Perturbation (RAP)), excluding parts of the signal with stationary sound pressure level (SPL), were analyzed with correlation analysis and statistical analysis (Analysis of Variance and subsequent multiple comparisons). Subjects shortened the requested task length by factor ≈ 0.5. The fo remained almost stable for most subjects and tasks. There were strong negative correlations between SPL and both OQ and ClQ. The median RAP appears to decrease towards the SPL apex and then increase again. Statistical effects were shown especially for females during the fast task, which may be due to raised SPL. There was no specific effect on stability found corresponding to the task's speed. Also, no major vocal instabilities at a specific sound pressure level were apparent, indicating no transitions as they exist for fo regions with registration events.